Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages RULES. 1. That this Society shall be called "THE UNITED BROTHERS' BIRMINGHAM BENEFIT SOCIETY," and shall consist of an unlimited number of members, to meet the first and third Saturdays in every month, from eight till ten o'clock, except during the months of January and February, when they shall meet from seven till ten o'clock. Its objects shall be to assist its members in sickness, and to provide for the payment of a sum of money at the death of a member or for the funeral expenses of a member's wife. No person to be admitted a member under 18, or above 35 years of age. Any person wishing to become a member must be medically examined by a doctor appointed by the society, the cost of such examination to be paid by the society. Each person on the night of proposition to deposit one shilling to the stock of the society. Members' contributions as follows, viz.: Sixpence per week to the sick fund, one shilling per quarter to the funeral fund, and fourpence per quarter secretary's salary. Members neglecting to clear the books on quarterly night to be fined sixpence; and if not cleared of all arrears on the first meeting night after quarterly night, such member shall be suspended from all benefits; and if such suspended member neglects to clear the books of the last quarter's arrears the fourth meeting night after quarterly night, he shall be excluded. Quarterly nights are the third Saturday in March, June, September, and December. 2. That no person can be admitted a member of this society until he has been proposed and seconded by two free members. He should attend on the next meeting night to be balloted for, and if approved of, he will be 345/7/2/2